Contra-Thermodynamic Positional Isomerization of Olefins - Zhao, Kuo; Knowles, Robert R. (Journal of the American Chemical Society, 2022)
A light-driven method for the contra-thermodynamic positional isomerization of olefins is described. In this work, stepwise PCET activation of a more substituted and more thermodynamically stable olefin substrate is mediated by an excited-state oxidant and a Bronsted base to afford an allylic radical that is captured by a Cr(II) cocatalyst to furnish an allylchromium-(III) intermediate. In situ protodemetalation of this allylchromium complex by methanol is highly regioselective and affords an isomerized and less thermodynamically stable alkene product. The higher oxidation potential of the less substituted olefin isomer renders it inert to further oxidation by the excited-state oxidant, enabling it to accumulate in solution over the course of the reaction. A broad range of isopropylidene substrates are accommodated, including enol ethers, enamides, styrenes, 1,3-dienes, and tetrasubstituted alkyl olefins. Mechanistic investigations of the protodemetalation step are also presented.